PENYELENGGARAAN PEMERINTAH DAERAH SERTA PENATAAN KELEMBAGAAN PEMERINTAH DAERAH - Reza Silvia; Margo Hadi Pura (IAIN Bengkulu, 2021)
Abstract: This paper aims to determine the implementation of local government and the institutional arrangement of local government. The method in this study uses a normative juridical approach. The normative juridical approach is an approach that is carried out based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research. The approach used in this research is to use a statutory approach. The technique of collecting primary legal materials and secondary legal materials uses the techniques of collecting legal materials with literature study. The results of this paper indicate that the implementation of regional government is based on the principle of decentralization and the application of the principle of co-administration. In a decentralized structure, lower-level government independently formulates and implements policies and interventions from higher levels of government. The existence of the delegation of authority to local governments is not something that the central government should be afraid of because the granting of authority will not be separated from coordination and supervision of the central government. In the administration of governmental authority carried out by the government, it must apply general principles of good governance, in this case the general principles of good governance are born from the practice of state and government administration so that it is not a formal product of a state institution such as law. Institutions are institutions that have great abilities in moving the organization, because institutions are formally arranged to produce rational actions in an organization. Institutions are means and tools in carrying out government activities in an increasingly complex society.Keywords: administration, structuring, institutional Abstrak: Tulisan ini bertujuan untuk mengetahui penyelenggaraan pemerintah daerah serta penataan kelembagaan pemerintah daerah. Metode dalam penelitian ini menggunakan pendekatan yuridis normatif. Pendekatan yuridis normatif adaah pendekatan yang dilakukan berdasarkan bahan hukum utama dengan cara menelaah teori-teori, konsep-konsep, asas-asas hukum serta peraturan perundang-undangan yang berhubungan dengan penelitian ini. Pendekatan yang digunakan dalam penelitian ini adalah dengan menggunakan pendekatan perundang-undangan. Teknik pengumpulan bahan hukum primer dan bahan hukum sekunder menggunakan teknik pengumpulan bahan hukum dengan studi pustaka. Hasil dari tulisan ini menunjukan bahwa penyelenggaraan pemerintah daerah berdasarkan asas desentralisasi dan penerapan asas tugas pembantuan. Dalam suatu struktur desentralisasi, pemerintah tingkat bawah merumusakan dan mengimplementasi kebijakan secara independen dan intervensi dari tingkatan pemerintahan yang lebih tinggi. Adanya pelimpahan kewenangan kepada pemerintah daerah tidak sebagai sesuatu yang harus ditakuti oleh pemerintah pusat karena pemberian kewenangan tersebut tidak akan terlepas dari koordinasi dan pengawasan pemerintah pusat. Dalam penyelenggaraan kewenangan pemerintahan yang dilakukan oleh pemerintahan harus menerapkan asas-asas umum pemerintahan yang baik dalam hal ini asas-asas umum pemerintahan yang baik lahir dari praktek penyelenggaraan negara dan pemerintahan sehingga bukan produk formal suatu lembaga negara seperti undang-undang. Kelembagaan merupakan lembaga yang memiliki kemampuan besar dalam menggerakan organisasi, karena kelembagaan ditata secara formal untuk melahirkan tindakan rasional dalam sebuah organisasi. Kelembagaan merupakan sarana dan alat dalam menjalankan kegiatan pemerintahan di era masyarakat yang semakin kompleks.Kata Kunci: penyelenggaraan, penataan, kelembagaan